Unveiling thermal dynamics: Integrated experimental and simulation insights into large-scale parallel pulsating heat pipe - Shilong Fan; Zhiming Xu; Wei Li; Fumin Shang; Hongliang Chang (Case Studies in Thermal Engineering)
The pulsating heat pipe (PHP) is an efficient passive heat transfer device that offers an effective solution for thermal management in proton exchange membrane fuel cells (PEMFCs). However, conventional single-side channel PHPs face significant challenges in PEMFC thermal management, including integration limitations, high start-up temperatures, and insufficient working fluid oscillation intensity. This study proposes an optimized configuration for PEMFC thermal management based on its structural characteristics: a large-scale parallel pulsating heat pipe (P-PHP) with bilaterally symmetric channels. The aim is to improve the thermal performance of PEMFCs. Results show that, in the x-axis orientation, the P-PHP exhibits remarkable adaptability to low heat input, achieving a rapid start-up time of just 205 s, while maintaining a temperature control threshold as low as 51.08 °C. The P-PHP also excels in fluid oscillation under low heat input conditions, making it well-suited for heat-sensitive scenarios. Furthermore, it demonstrates excellent heat transfer performance, with a 40 % decrease in thermal resistance in the x-axis orientation compared to other orientations. These results offer valuable insights and new solutions for optimizing PEMFC thermal management, thereby contributing to the advancement of fuel cell technology commercialization.